2018
DOI: 10.1080/13102818.2018.1502051
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of DDT by gold nanoparticles synthesised using Lawsonia inermis for environmental safety

Abstract: Metallic gold nanoparticles (AuNPs) were prepared and stabilised with henna (Lawsonia inermis) extract. The synthesis of AuNPs was characterised by ultraviolet-visible (UV-Vis) spectrophotometry, transmission electron microscopy (TEM), scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDS), dynamic light scattering and Fourier-transform infrared spectroscopy (FTIR). This study also investigated the degradation of dichlorodiphenyltrichloroethane (DDT) using AuNPs. The initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…An in-depth examination of the aggregates revealed that the generated nanoparticles were not in direct physical contact with one another. This finding is consistent with the notion that phytoconstituents were responsible for the stabilisation of AgNPs [ 32 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An in-depth examination of the aggregates revealed that the generated nanoparticles were not in direct physical contact with one another. This finding is consistent with the notion that phytoconstituents were responsible for the stabilisation of AgNPs [ 32 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The AgNPs based on the peels of banana, orange, mandarin, and kivi fruit was reported by Abd El-Aziz et al [ 41 ], a colour shifted from yellow to a dark brown with increasing intensity. Within 72 h, a noticeable alteration occurred [ 41 , 42 ]. The size, shape, and yield of synthesized NPs are all affected by the shift in pH, which in turn affects plant metabolism and the plant's capacity to chelate and reduce metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradation has been recognized as a cost-effective, safe, and promising method for the removal or detoxification of hazardous organic compounds (Abd-ElHaleem et al, 2002 , 2003 ). In light of this, Abd-Elaziz et al ( 2018 ) prepared and stabilized AuNPs with HLE, hypothesizing potential applicability for bioremediation processes involving dichlorodiphenyltrichloroethane (DDT). Degradation experiments, conducted at DDT concentrations of either 10 or 20 mg/l, revealed a maximum DDT degradation of 64.1% at 10 mg/l and 77.4% at 20 mg/l after 72 h of incubation.…”
Section: Bioremediation Of Hazardous Organic Compoundsmentioning
confidence: 99%
“…An alternative method for the pesticide elimination in the environment is the use of nanotechnology, such as nanoparticles (NPs), , nanocomposites, , metal NPs, , bi-metallic NPs, , and metal oxide NPs. , Some nanomaterials that display plasmonic effects are very promising in the photoinduced POP degradation. One of the most outstanding properties of these nanomaterials is that they can support localized surface plasmons (LSPs) that can be excited by using a light of an adequate wavelength, leading to LSP resonance (LSPR), which is an effect derived from the interaction of the resonant radiation with the free electrons.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method for the pesticide elimination in the environment is the use of nanotechnology, such as nanoparticles (NPs), 20 , 21 nanocomposites, 21 , 22 metal NPs, 23 , 24 bi-metallic NPs, 25 , 26 and metal oxide NPs. 27 , 28 Some nanomaterials that display plasmonic effects are very promising in the photoinduced POP degradation.…”
Section: Introductionmentioning
confidence: 99%